Business Justice Principle in the Indonesian Airport Sector - Negara, Dharma Setiawan; Saputra, Rio; Darmawan, Didit; Hardyansah, Rommy; Wibowo, Agung Satryo (Journal of Posthumanism, 2024)
Increasing competition in the aviation business has resulted in a shift in the trend of airport business management from monopoly to privatization. In contrast, practice in Indonesia shows that the airport sector is still centralized-monopolistic. PT. Angkasa Pura I (Persero) and PT. Angkasa Pura II (Persero) is a monopoly company that manages airport services and airport-related services at several airports in Indonesia. Based on the KPPU’s decisions, the two companies, which should be excluded from the application of the Business Competition Law, were proven to have abused monopoly power by creating barriers to entry for other business actors. This research aims to analyze the application of the principles of justice in doing business in the airport sector in Indonesia. The principle of business justice is an essential concept in creating a fair, transparent and sustainable business environment. In the airport sector, the application of this principle includes aspects such as regulation, accessibility, healthy competition and protection of the rights of consumers and business actors. Implementation of the principles of business justice in the airport sector, including by improving regulations, increasing transparency and accountability, as well as strengthening supervision of business practices. In this way, it is hoped that the airport sector in Indonesia can develop more fairly and sustainably, providing maximum benefits for all stakeholders.